OP21 Effectiveness and cost-utility of a group self-management support intervention (COPERS) for people with chronic musculoskeletal pain: a randomised controlled trial. (2nd September 2014) - Eldridge, S; Spenser, A; Pincus, T; Rahman, A; Bremner, SA; Underwood, MR; Taylor, SJC; Carnes, D; Homer, K; Kahan, BC; Hounsome, N; Diaz-Ordaz, K
Abstract : Background: Chronic musculoskeletal pain is a common problem. Pharmacological approaches are often ineffective and there are concerns about side effects or dependence. Non-pharmacological interventions may enable patients to manage their condition better but there is limited evidence for their effectiveness. We evaluated a novel, theoretically grounded self-management support intervention for chronic musculoskeletal pain. Methods: COPERS is an evidence-based, group intervention consisting of 24 components delivered over three days with a top up two weeks later. The course is informed by cognitive behaviour therapy and aims to increase self-efficacy to manage chronic pain. It is facilitated by a health care professional and a lay individual. We conducted a pragmatic, multi-centre, individual patient randomised controlled trial comparing COPERS with usual care and a relaxation CD. Participants were recruited from primary care or physiotherapy services in east London and the Midlands and randomised to intervention or control (allocation ratio 1.33:1) using varied permuted blocks and strict allocation concealment. We collected follow up data at six and 12 months. Our primary outcome was pain related disability (Chronic Pain Grade, CPG, subscale) at 12 months. We also measured: costs, health utility (EQ-5D), anxiety, depression (Hospital Anxiety and Depression Scale, HADS), coping, pain acceptance and social integration. Results: We recruited 703 participants, mean age 59.9 years, 81% white, 67% female, 23% in employment; 85% with pain for at least three years, 23% on strong opioids. Symptoms of depression and anxiety were common (mean HADS scores 7.4 [SD 4.1] and 9.2 [4.6], respectively). Overall intervention participants received 85% of course content. At 12 months there was no significant difference between treatment groups in CPG disability (difference -1.0, intervention vs. control, 95% CI -4.9 to 3.0). However self-efficacy, anxiety, depression, pain acceptance and social integration were significantly better in the intervention group at six months and these differences remained significant at 12 months for depression and social integration. COPERS has a high probability (>79%) of being cost-effective compared to usual care at a threshold of £30, 000 per quality adjusted life year. Conclusion: COPERS improved psychological wellbeing, and is likely to be cost effective by current NICE criteria but failed to influence our primary outcome of pain related disability. In the absence of more effective group self-management interventions, COPERS could be used as a substitute for less well evidenced (and more expensive) pain self-management programmes. However, effective interventions to improve hard outcomes, such as disability, in chronic pain patients are still required. Acknowledgement: This project was funded by the National Institute for Health Research (NIHR) under its Programme Grants for Applied Research scheme (RP-PG-0707–10189). This project also benefited from facilities funded through the Birmingham Science City Translational Medicine Clinical Research and Infrastructure Trials Platform, with support from Advantage West Midlands.